Correlations between cognitive reserve, gray matter, and cerebrospinal fluid volume in healthy elders and mild cognitive impairment patients - Zhou, Liang; Yang, Wenxia; Liu, Yang; Li, Jiachen; Zhao, Mengmeng; Liu, Guangyao; Zhang, Jing (Frontiers in Neurology, 2024)
Objective: To explore the effect of cognitive reserve (CR) on brain volume and cerebrospinal fluid(CSF)in patients with mild cognitive impairment (MCI) and healthy elders (HE).: 31 HE and 50 MCI patients were collected in this study to obtain structural MRI, cognitive function and composite CR scores. Educational attainment, leisure time and working activity ratings from two groups were used to generate cognitive reserve index questionnaire (CRIq)scores. The different volumes of brain regions and CSF were obtained using uAI research portal in both groups, which were taken as the regions of interest (ROI), the correlation analysis between ROIs and CRIq scores were conducted. Results: The scores of CRIq, CRIq-leisure time, and CRIq-education in HE group were significantly higher than patients in MCI group, and the montreal cognitive assessment (MoCA) and minimum mental state examination (MMSE) scores were positively correlated with the CRIq, CRIq-education in both groups, and were positively correlated with CRIq-leisure time in MCI group. The scores of auditory verbal learning test (AVLT) and verbal fluency test (VFT) were also positively correlated with CRIq, CRIq-leisure time and CRIq-education in MCI group, but the score of AVLT was only positively correlated with CRIq in HE group. Moreover, in MCI group, the volume of the right middle cingulate cortex and the right parahippocampal gyrus were negatively correlated with the CRIq, and the volume of CSF, peripheral CSF and third ventricle were positively correlated with the CRIq-leisure time score. The result of mediation analysis suggested that right parahippocampal gryus mediated the main effect of the relationship between CRIq and MoCA score in MCI group. Conclusion: People with higher CR show better levels of cognitive function, and MCI patients with higher CR showed more severe volume atrophy of the right middle cingulate cortex and the right parahippocampal gyrus, but more CSF at a given level of global cognition.